The hygienist and sociologist Louis-René Villermé (1782-1863): a pioneer of occupational medicine / L’igienista e sociologo Louis-René Villermé (1782-1863): un pioniere della medicina del lavoro - Tsoucalas, G.; Kousoulis, A.A.; Karamanou, M.; Stamboulis, E.; Androutsos, G. (La Medicina del Lavoro, 2012)
Background: Louis-René Villermé’s work and research have ranked him among the most important figures in the history of occupational medicine. Objectives: The aims of this article were to objectively record the influence and the impact of Villermé’s life and work on the establishment of occupational medicine. Methods: A thorough analysis of scientific and historical literature on the subject was conducted. The authors paid special attention to primary French sources. Results: Louis-René Villermé was born in Paris in 10 March 1782. Taking advantage of his good fortune and financial prosperity, due to the recognition of his initial work, he progressed efficiently and with decision towards a new way of thinking. He stressed the importance of observation of the social environment, the role of investigations on lack of hygiene, the significance of statistical recording and the study of demographic statistics, and devoted himself to the labour force’s health problems. He died in his homestead on 16 November 1863. Conclusions: Villermé lived an intense life full of activity, social work and travel. His support of the working classes’ rights, his opposition to child labour and gender inequality, and his fight for humane conditions in prisons remain diachronic ideals. He provided a reference model for socio-medical research and contributed to the establishment of the new scientific discipline, Occupational Medicine.RiassuntoL’igienista e sociologo Louis-René Villermé (1782-1863): un pioniere della medicina del lavoroIntroduzione: Il lavoro e la ricerca di Louis-René Villermé lo promuovono tra le figure più importanti nella storia della medicina del lavoro. Obiettivi: Gli obiettivi di questo articolo sono quelli di riconoscere l’influenza e l’effetto della vita e dell’opera di Villermé nella nascita della medicina del lavoro. Metodi: È stata condotta un’analisi approfondita della letteratura scientifica e storica. Gli autori hanno prestato una attenzione particolare alle fonti primarie francesi. Risultati: Louis-René Villermé è nato à Parigi il 10 marzo 1782. Disponendo di una buona prosperità finanziara e grazie al riconoscimento del suo lavoro iniziale, è riuscito a proporre con decisione e in modo efficiente un nuovo modo di pensare. Ha sottolineato l’importanza dell’osservazione del contesto sociale, il ruolo delle indagini di igiene, il significato delle rilevazioni statistiche  e lo studio delle statistiche demografiche e si è consacrato ai problemi sanitari della forza lavoro. Muore nella sua casa il 16 Novembre 1863. Conclusioni: Villermé ha vissuto una vita intensa, piena di azioni, di lavoro sociale e di viaggi. La sua difesa dei diritti delle classi popolari, la sua opposizione al lavoro dei minori ed alle differenze di genere, la sua lotta  per il miglioramento delle condizioni nelle prigioni restano degli ideali diacronici.